2008
DOI: 10.4049/jimmunol.180.5.2757
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TGF-β-Induced Expression of Foxp3 in T cells Is Mediated through Inactivation of ERK

Abstract: The peripheral induction of T regulatory cells can be accomplished by TGF-β through an epigenetic regulation leading to the expression of Foxp3. However, the exact mechanism of such a TGF-β-mediated action remains unclear. In the current study, we found that TGF-β treatment of CD4+CD25− T cells during T cell activation led to a transient inhibition of the phosphorylation of ERK followed by the induction of Foxp3 expression in these cells. Direct treatment with a specific ERK inhibitor, UO126, during CD4+CD25− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 27 publications
6
59
1
Order By: Relevance
“…This is consistent with a previous report that ERK1/2 inhibition promotes FOXP3 induction (24). However, these data do not preclude a role for other pathways.…”
Section: Discussionsupporting
confidence: 83%
“…This is consistent with a previous report that ERK1/2 inhibition promotes FOXP3 induction (24). However, these data do not preclude a role for other pathways.…”
Section: Discussionsupporting
confidence: 83%
“…However, acquisition of the T reg phenotype does not exclusively mean the conversion of T reg from human T cells because we also observed a population of nonsuppressive T cells with the phenotype of T reg in the absence of AT, and previous research has reported a tran- pathways, which regulate FoxP3 expression in activated naïve T cells ( 37,38 ), have been demonstrated to be regulated by AT in some systems ( 39,40 ). In our study, we observed that AT inhibited the phosphorylation of ERK and PI3K-Akt-mTOR and U0126 (ERK inhibitor) or LY294002 (PI3K-Akt inhibitor) treatment of activated primary T cells mimicked the effects of AT on T reg .…”
Section: Downloaded Frommentioning
confidence: 80%
“…PARP-1 might regulate Foxp3 gene expression by acting on chromatin structure, by regulating the activity of transcription factors, or by modulating signal transduction events (31). PARP-1 was described to interact with and be phosphorylated by Erk1/2 (32, 33), which also plays a role in Treg cell differentiation (34). Differences between the results obtained in experiments with PARP-1 KO mice and with the use of PARP inhibitors demonstrated that PARP-1 can regulate the activity of target molecules by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%